THE EFFECT OF SEAWEED FLOUR (Gracilaria verrucosa) SUBSTITUTION ON THE QUALITY CHARACTERISTICS AND FIBER CONTENT OF BISCUITS - Cahya, Ira Cindy Dwi; Agustini, Tri Winarni; Anggo, Apri Dwi (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2025)
Biscuits with specific treatments can become functional foods made from wheat flour and are often consumed as snacks. Biscuits usually contain high carbohydrates and fats, but low protein and fiber. G. verrucosa is a red algae rich in dietary fiber (53.57%). Adding G. verrucosa flour to biscuits can increase the natural fiber content, and be an alternative nutritious and affordable product. This study aims to determine the effect of seaweed flour substitution as a reference for high-fiber biscuits, quality characteristics and nutritional content, and the best concentration based on sensory tests. The research method for this biscuit was carried out experimentally in the Laboratory using a completely randomized design (CRD) consisting of 4 treatments and 3 replications of RL (0%), RL (2%), RL (4%) and RL (6%). Research parameters observed include : protein content, fat content, moisture content, ash content, food fibre, texture, color test and sensory analysis. Data analysis were carried out using SPSS 16 software. Parametric data were analyzed using ANOVA, Duncan and Independent Sample T-test (food fibre, while non-parametric data were analyzed using Kruskall-Wallis and Mann-Whitney tests. The results of the study showed that the higher the concentration of G. verrucosa flour substituted into biscuits, the more it would increase the nutritional content, such as protein, fat, moisture, ash, fiber and texture that met the requirements of SNI 2973:2022. In addition, it reduces the carbohydrate value and sensory characteristics such as a darker color and distinctive odor. The best results were the RL (4%) treatment with dietary fiber (3.52%), protein (8.58%), water (3.54%), fat (22.34%), ash (1.71%), carbohydrates (63.84%), crispness (629.42 gf - more cryspy), and color with L* values 53.28, a* (-10.35), b* 19.21, and panelist sensory had a 95% confidence interval of 7.83 <µ <8.26.